A calcium looping process for simultaneous CO2 capture and peak shaving in a coal-fired power plant - Zhou, Linfei; Duan, Lunbo; Anthony, Edward J. (Elsevier, 2018)
CO2 capture and peak shaving are two of the main challenges for coal-fired power plants in China. This paper proposed a calcium looping (CaL) combustion system with cryogenic O2 storage for simultaneous flue gas decarbonization and peak shaving for a 1000 MWe coal-fired power plant. The philosophy of this concept is that: (1) the boiler always operates at maximum continuous rating (MCR) to ensure the highest boiler efficiency; (2) during off-peak times, the excess energy output from coal combustion is used to provide heat for the calciner and produce pure oxygen for energy storage; (3) at peak times, the O2 produced is used to capture CO2 in the flue gas via the CaL process and reduce the CO2 abatement penalty; and (4) any excess O2 is treated as a by-product for commercial utilization. The whole system was simulated in Aspen Plus® which shows that the net electric efficiency of the proposed system without cryogenic O2 storage system is 35.52%LHV (LHV, low heating value), while that of the conventional CaL system is 34.54%LHV. The proposed system can reduce the methane consumption rate by 38.5 t/h when methane is used as fuel in the calciner. Including the cryogenic O2 storage system, the peaking capability of the proposed system can range from 534.6 MWe to 1041 MWe. Correspondingly, the net electric efficiency is improved from 18.98%LHV to 36.97%LHV. Increasing the rate of oxygen production can reduce the minimum net power output to lower than 534.6 MWe. The peaking capability can be regulated by the rate of oxygen production where excess oxygen serves as a byproduct.
Keywords: CO2 capture; Coal-fired power plants; Calcium looping; Cryogenic O2 storage system; Peak shaving